FORMULASI RAGI CAMPURAN UNTUK PRODUKSI BIOETANOL DARI LIMBAH KAYU SENGON - Ina Winarni; Sri Komarayati; Djarwanto (BRIN Publishing, 2017)
Currently, bioethanol is one of biofuels which is potentially developed for new and renewable alternative energy. Bioethanol could be fermented from agriculture and forest wastes, with pre-treatment and hydrolysis process before the fermentation. Those process could be carried out by an addition of microbe (yeast). In order to gain greater ethanol content, yeast mixing formulation is crucial to obtain optimum ethanol content. This paper studies the formula of yeast mixing for optimum ethanol production of sengon wood waste. Formulation was conducted by mixing Aspergillus oryzae, Saccharomyces cerevisae, Rhyzopus oryzae and other substances with various treatments. Commercial yeast of 3 – 9% Sacharomyces cerevisae was used as a comparable control. Results showed that 7% yeast mixing was effective to produce 1.569% ethanol content from lignocellulose fermentation. The ethanol content is relatively greater than those of commercial yeast which constitutes of about 0.652% ethanol content.